2021
DOI: 10.3390/ijms222111510
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of CMML

Abstract: Chronic myelomonocytic leukemia (CMML) is a rare and challenging type of myeloproliferative neoplasm. Poor prognosis and high mortality, associated predominantly with progression to secondary acute myeloid leukemia (sAML), is still an unsolved problem. Despite a growing body of knowledge about the molecular repertoire of this disease, at present, the prognostic significance of CMML-associated mutations is controversial. The absence of available CMML cell lines and the small number of patients with CMML make pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Comprehensive information about clonal evolution from CMML to AML is still lacking. A few sequential studies comparing paired patient samples at the time of CMML diagnosis and at AML transformation have postulated a key role for the RAS pathway and for mutations in EZH2, IDH1/2, NPM1 , and FLT3 -ITD [ 14 , 50 ]. Patel et al [ 16 ] suggested that TET2, ASXL1 , and SRSF2 were ancestral mutations present in early stages of CMML and that KRAS, NRAS, RUNX1, U2AF1 , and CBL mutations were secondary events leading to AML transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive information about clonal evolution from CMML to AML is still lacking. A few sequential studies comparing paired patient samples at the time of CMML diagnosis and at AML transformation have postulated a key role for the RAS pathway and for mutations in EZH2, IDH1/2, NPM1 , and FLT3 -ITD [ 14 , 50 ]. Patel et al [ 16 ] suggested that TET2, ASXL1 , and SRSF2 were ancestral mutations present in early stages of CMML and that KRAS, NRAS, RUNX1, U2AF1 , and CBL mutations were secondary events leading to AML transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Even though animal models are valuable tools for research, the expenditure is high, drug screening requires a large amount of animals and, biologically, model animals cannot completely mimic human BM microenvironments. These issues emphasize the need for better strategies to improve human systems modeling in vivo; in this context, new results and extensive reviews regarding animal models for leukemic research are periodically published [127,129,[136][137][138][139][140][141][142][143][144][145][146]. The graph is based on [129], with additional information from [145,[147][148][149].…”
Section: In Vivo Rodent Modelsmentioning
confidence: 99%